1999
DOI: 10.1016/s0014-5793(99)00170-2
|View full text |Cite
|
Sign up to set email alerts
|

A function for the vitamin E metabolite α‐tocopherol quinone as an essential enzyme cofactor for the mitochondrial fatty acid desaturases

Abstract: A critical analysis of the changes in fatty acid patterns and their metabolism elicited by vitamin E deficiency leads to the proposal that a major role of dietary RRR-K Ktocopherol (K K-TOC) is as an enzymatic precursor of K Ktocopherolquinone (K K-TQ) whose semiquinone radical functions as an essential enzyme cofactor for the fatty acid desaturases of the recently elucidated carnitine-dependent, channeled, mitochondrial desaturation-elongation pathway; a detailed mechanism for its function is proposed. Pathop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
11

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 80 publications
2
32
0
11
Order By: Relevance
“…The effects of vitamin E and selenium on the fatty acid profile of chicken tissues are rather conflicting. It was argued that α-tocopherol and Se may protect PUFA from oxidation, avoiding their loss, or may promote fatty acid synthesis by a positive effect on the activity of ∆4-, ∆5-, ∆6-desaturases and elongases, enzymes involved in the processes leading to LC-PUFA formation (Infante, 1999). Some authors showed that dietary selenium did not influence LC-PUFA levels (Bou et al, 2005;Nyquist et al, 2013) in broiler meat.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of vitamin E and selenium on the fatty acid profile of chicken tissues are rather conflicting. It was argued that α-tocopherol and Se may protect PUFA from oxidation, avoiding their loss, or may promote fatty acid synthesis by a positive effect on the activity of ∆4-, ∆5-, ∆6-desaturases and elongases, enzymes involved in the processes leading to LC-PUFA formation (Infante, 1999). Some authors showed that dietary selenium did not influence LC-PUFA levels (Bou et al, 2005;Nyquist et al, 2013) in broiler meat.…”
Section: Discussionmentioning
confidence: 99%
“…E vitamini yetersizliği durumunda artan lipit peroksidasyonu, E vitamininin esansiyel kofaktör fonksiyonlarının bozulduğu düzeylere kadar tüketilmesine yol açabilir 2 . Başlıca yağda çözünebilen bir antioksidan olan E vitamini, dokularda lipoperoksitlerin sentezi ve birikimine karşı korunmanın önemli bir bileşeni olarak, demir birikiminden dolayı meydana gelebilecek doku patolojisini de azaltır 19 . E vitamini büyüme, üreme, çeşitli hastalıkların önlenmesi ve dokuların bütünlüğünün korunması gibi vücut fonksiyonları için gereklidir.…”
Section: E Vitamininin Etkileriunclassified
“…Yapılan bir çalışmada diyetteki α-tokoferol de tavşanlarda hipokolesterolemik bir etkiye yol açmıştır 22 . E vitamini steroid hormon üreten dokularda yoğun olarak bulunur ve bu dokularda sitokrom p-450'nin oldukça duyarlı steroidojenik aktivitelerini, lipit peroksidasyonuna karşı korur 19 . Lipoprotein reseptörlerinin sentezinin α-tokoferol tarafından düzenlendiği bildirilmiştir 9 .…”
Section: E Vitamininin Etkileriunclassified
See 2 more Smart Citations